Corruption Factors and Discretion of the Law Enforcement Agency - Vladimir Valentinovich Kozhevnikov; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
The article analyzes the corruption-generating factors enshrined in official legal documents—the Federal Law of the Russian Federation "On Anti-Corruption Expertise of Regulatory Legal Acts and Draft Regulatory Legal Acts" dated June 17, 2009, and the Methodology for Conducting Anti-Corruption Expertise of Regulatory Legal Acts and Draft Regulatory Legal Acts" approved by the Decree of the Government of the Russian Federation dated February 26, 2010. Particular attention is paid to such a corruption-generating factor as the wide margin of discretion (breadth of discretionary powers) of the law enforcement agency. In this regard, the discretion of the subjects of the law enforcement process is analyzed, the necessity, significance, as well as both subjective and objective limits of it are argued. With regard to the former, it is substantiated that the latter should be considered not as the legal consciousness or professional culture of the subjects of law enforcement, but their professional culture. Objective limits are determined by optional legal norms containing evaluative concepts. As an example, several provisions of the Criminal Procedure Code of the Russian Federation are cited, which necessarily presuppose the discretion of law enforcement agencies in the law enforcement sphere.